2010
DOI: 10.1111/j.1464-410x.2010.09513.x
|View full text |Cite
|
Sign up to set email alerts
|

Findings of fat‐suppressed T2‐weighted and diffusion‐weighted magnetic resonance imaging in the diagnosis of non‐palpable testes

Abstract: RESULTSIn the 63 non-palpable testes, MRI identified 22% (14/63) as intra-abdominal, 20% (13/63) as intra-canalicular, 29% (18/63) as testicular nubbins, and 29% (18/63) as unidentifiable. Although it was difficult to confirm their presence in the abdominal cavity using T1-and T2-weighted imaging alone, additional assessment, including fatsuppressed T2-weighted imaging and DWI facilitated the detection of intra-abdominal testes more easily because they were imaged at a markedly higher signal intensity. The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…Combination of conventional MRI and other forms of MRI such as fat-suppressed T2-weighted MRI, diffusionweighted MRI, or MRA improves false-negative rates and increase the sensitivity in order to make this form of imaging more reliable in assessing boys with cryptorchidism (18,23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of conventional MRI and other forms of MRI such as fat-suppressed T2-weighted MRI, diffusionweighted MRI, or MRA improves false-negative rates and increase the sensitivity in order to make this form of imaging more reliable in assessing boys with cryptorchidism (18,23,24).…”
Section: Discussionmentioning
confidence: 99%
“…A few recently published reports have addressed the diagnostic performance of DWI in the evaluation of various scrotal pathologies such as detection and localization of impalpable testes, diagnosis of testicular torsion and differentiation between normal, benign and malignant scrotal contents (9,(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…DWI with calculation of ADC represents an important adjunct, providing quantitative information regarding structural tissue changes at a cellular level and therefore helping in tissue characterization [22][23][24]. Recent reports have addressed on the diagnostic performance of DWI in the evaluation of scrotal diseases, including differentiation between normal, benign and malignant scrotal contents, detection and localization of impalpable testes and diagnosis of testicular torsion [24,[28][29][30]. In a previous retrospective study, we reported an accuracy of 91%, 87% and 100% in the characterization of intratesticular lesions, when using conventional MRI sequences alone, DWI alone and DWI combined with conventional sequences, respectively [24].…”
Section: Discussionmentioning
confidence: 99%
“…When the testicles were located in the inguino-scrotal area, however, ultrasound demonstrated a 92% accuracy rate compared with 83% for MRI. 6 MRI in combination with fat-suppressed T2-weighted images 6,20 and diffusionweighted imaging 6,[20][21] has been shown to improve not only the overall accuracy rate of prediction up to 98.4% but also perform effectively with a high sensitivity rate of 100% for locating intraabdominal testicles. 6,20 …”
Section: Figurementioning
confidence: 99%